Effect of Ionic Liquids on the Physical Properties of the Newly Synthesized Conducting Polymer - Dong Uk Lee; Jin Yeong Jeong; Ji Woong Han; Gi-Chung Kwon; Pankaj Attri; In Tae Kim (International Journal of Polymer Science)
Conducting polymer has many applications in electronics, optical devices, sensors, and so on; however, there is still a massive scope of improvement in this area. Therefore, towards this aim, in this study, we synthesized a new thiophene-based conducting polymer, 2-heptadecyl-5-hexyl-6-(5-methylthiophen-2-yl)-4-(5-((E)-prop-1-enyl)thiophen-2-yl)-5H-pyrrolo[3,4-d]thiazole (HHMPT). Further, to increase its application, the interactions between the conducting polymer (HHMPT) and ionic liquids (ILs) were investigated by UV-Vis spectroscopy, FTIR spectroscopy, and confocal Raman spectroscopy techniques. Moreover, film roughness and conductivity of the polymer film with or without ILs were also studied. The imidazolium- and ammonium family ILs with the potential to interact with the newly synthesized conducting polymer were used. The results of the interaction studies revealed that the imidazolium family IL-polymer mixtures and ammonium family IL-polymer mixtures have almost similar conductivity at low concentration of ILs. This study provides an insight into the combined effect of a polymer and ILs and may generate many theoretical and experimental opportunities.